2016
DOI: 10.1021/acs.organomet.6b00070
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Reactions of Diruthenium Tetrahydride Complexes: Carbon–Hydrogen Bond Cleavage of Tetrahydrofuran Leading to Bridging Cyclic Fischer-Type Carbene Complexes

Abstract: Photochemical reactions of diruthenium tetrahydride complexes containing cyclopentadienyls as auxiliary ligands, CpsRu­(μ-H)4RuCps (1) (a: Cps = C5Me5 (Cp*), b: C5EtMe4 (CpEt), and c: 1,2,4-C5(t-Bu)3H2 (Cp‡)), with tetrahydrofuran were studied for elucidation of the reaction mode of dinuclear complexes containing multiple bridging hydrides. Complexes 1a–c reacted with tetrahydrofuran under UV irradiation (365 nm) to produce bridging cyclic Fischer-type carbene complexes, {CpsRu­(μ-H)}2(μ-cyclo-CCH2CH2CH2O−)­(μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…This can alter the reaction mechanism and often provides very active species, as seen in the field of palladium phosphane chemistry . We reported the synthesis of a diruthenium complex, Cp ‡ Ru­(μ-H) 4 RuCp ‡ ( 1 ; Cp ‡ = 1,2,4-C 5 t Bu 3 H 2 ), supported by bulky Cp ‡ groups, whose steric demand effectively prevented the condensation of the dinuclear complex to a tetranuclear skeleton …”
supporting
confidence: 58%
See 1 more Smart Citation
“…This can alter the reaction mechanism and often provides very active species, as seen in the field of palladium phosphane chemistry . We reported the synthesis of a diruthenium complex, Cp ‡ Ru­(μ-H) 4 RuCp ‡ ( 1 ; Cp ‡ = 1,2,4-C 5 t Bu 3 H 2 ), supported by bulky Cp ‡ groups, whose steric demand effectively prevented the condensation of the dinuclear complex to a tetranuclear skeleton …”
supporting
confidence: 58%
“…t Bu 3 H 2 ), supported by bulky Cp ‡ groups, 2 whose steric demand effectively prevented the condensation of the dinuclear complex to a tetranuclear skeleton. 3 Steric repulsion also influences the coordination mode of substrates at a multimetallic site. We have shown that a triruthenium complex, {Cp*Ru(μ-H)} 3 (μ 3 -H) 2 (Cp* = C 5 Me 5 ), reacts with primary silanes to yield an equilibrated mixture of μ 3 -η 2 :η 2 :η 2 -silane and μ 3 -η 2 :η 2 -silyl complexes.…”
mentioning
confidence: 99%
“…9,10 The past few years have also seen important progress in the photochemistry of complexes with bridging hydrides. 11,12 The production of hydrogen by photocatalytic methods is of enormous current interest, but the vast majority of approaches involve neither photochemical reaction of metal hydride complexes directly nor formation of excited states of metal hydride complexes by photosensitization. The involvement of hydrides in the photocatalytic splitting of water, typically by protonation of an intermediate, is reviewed elsewhere, 13−17 and a very different approach will be taken here.…”
mentioning
confidence: 99%
“…We speculate that the formation of catalytically inactive species as a consequence of oxygen atom directed reactions is responsible for this failed reaction. We have previously shown that 1 reacts with tetrahydrofuran to yield a μ-oxycarbene complex …”
mentioning
confidence: 68%
“…We have previously shown that 1 reacts with tetrahydrofuran to yield a μ-oxycarbene complex. 11 The stoichiometric reaction of 1 with cyclic amines was then investigated to elucidate the mechanism. Complex 1 reacted with hexamethylenimine at 160 °C to afford the μ-cyclic imine complex 2 in 71% yield (eq 1).…”
mentioning
confidence: 85%